(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study aimed to develop Bovine Colostrum Milk powder for autism children to improve their immunity. Autism is a complex and clinically heterogeneous disorder with a spectrum of symptoms. Although autism affects primarily brain function (especially affect, social functioning, and cognition), it is unknown to what extent other organs and systems are disrupted. Bovine colostrum is a milky fluid that comes from the breasts of cows the first few days after giving birth, before true milk appears. It contains proteins, calcium, vitamins and minerals. Antibody levels in bovine colostrum can be 100 times higher than levels in regular cow’s milk. Since the bovine colostrum is also loaded with nutrients that promote growth, it boosts immunity, treats infections and offer more benefits for humans especially for autism children. The sample is prepared by boiling the Bovine Colostrum milk and drying it at sunlight for 5-6 hours. The dried sample is then made into fine powder, it is then added with sugar powder, cocoa powder and cardamom powder to enhance the flavor. The sensory evaluation was done using a 5 point hedonic scale with the help of seven experts and the results were computed accordingly. The microbial analysis was carried out and absence of fungi, yeast and moulds were noted. The Nutritive analysis was carried out for calories, carbohydrates, protein, calcium, iron, zinc and fat. These nutrients are present in high amounts whereas microbial count of yeast and moulds were absent. Bovine Colostrum powder was popularized to the autism children’s parents at Thoothukudi.